A Social Phenomenology of Non-Player Characters (NPCs) in Videogames. - Scriven, Paul (Techné: Research in Philosophy & Technology, 2023)
Non-player characters (NPCs) are a common feature in contemporary videogames, particularly role-playing games (RPGs). Evidence suggests player relationships with these fictional, digital characters can manifest as deeply emotional experiences that can 'bleed' off the screen and affect the daily lives of players. However, research in this area is still in its infancy, and as yet has not been given a thorough conceptual treatment. Applying the sociological phenomenology of Alfred Schütz, this paper will examine the structure of the experiences that players have with NPCs, and how these experiences manifest as meaningful social experiences. By a reconceptualization of the player-NPC relationship as a deeply mediated human-human relationship, this paper aims to build a foundation for further phenomenological study into how players engage with fictional characters in immersive videogame worlds.